2009
DOI: 10.1007/s00467-008-0975-y
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory blood pressure monitoring in healthy children with parental hypertension

Abstract: The aim of this study was to compare ambulatory blood pressure monitoring (ABPM) parameters in offspring with at least one hypertensive parent (HP) to offspring with normotensive parents (NP) and to determine whether gender of parent or child might influence the association between parental hypertension and blood pressure (BP). Eighty-nine healthy children (mean age 11.1 +/- 3.9 years) with HP and 90 controls (mean age 10.5 +/- 3.1 years) with NP were recruited. Age, gender, and height did not differ between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
1
8
0
1
Order By: Relevance
“…In the study by Ravogli et al [12], involving young adults, and in the study by Alpay et al [15], involving children with a positive family history of hypertension, nocturnal and average SBP values were significantly higher in these populations compared to those with a negative family history for hypertension. In these studies, the authors emphasized the fact that in healthy children with a positive family history of hypertension, ABPM allows detection of early changes.…”
Section: Discussionmentioning
confidence: 85%
“…In the study by Ravogli et al [12], involving young adults, and in the study by Alpay et al [15], involving children with a positive family history of hypertension, nocturnal and average SBP values were significantly higher in these populations compared to those with a negative family history for hypertension. In these studies, the authors emphasized the fact that in healthy children with a positive family history of hypertension, ABPM allows detection of early changes.…”
Section: Discussionmentioning
confidence: 85%
“…Family history of HTN or CV disease may identify children and adolescents with essential HTN, but history of hereditary diseases associated with secondary forms of HTN should also be relevant (1,37). Parental history of HTN has been associated with masked HTN, early TOD, changes in central and peripheral hemodynamics, and can guide further evaluation (79,(93)(94)(95). A complete clinical history assessment may include information summaraised in Table 4.2.1.…”
Section: Family and Clinical Historymentioning
confidence: 99%
“…Recent studies of healthy adolescents have shown that if either parent is hypertensive, their own ABPM data are also higher both in terms of daytime and nighttime systolic and diastolic BPs [51] . Parental BP is a strong predictor of their children's BP in the future.…”
Section: Special Applications Of Abpmmentioning
confidence: 99%